Choosing Faith and Quality: Biographical Stories of Parents Navigating Islamic School Service Management and Marketing Narratives - Candra Mochamad Surya; Rusdi Bin Jamaludin (International Journal of Educational Narratives, 2026)
Background. Increasing competition among Islamic elementary and early childhood education institutions demands innovative management strategies to maintain their existence. In the industrial area of ??East Karawang District, this situation is exacerbated by the rapid growth of educational institutions and the growing urban population. As a result, disparities have emerged between institutions, with some experiencing an increase in student enrollment, while others are experiencing a decline in interest due to uneven service standards. Purpose. This study aims to analyze educational service management as a strategy for recruiting new students from an Islamic perspective in Islamic Elementary Schools (Madrasah Ibtidaiyah) and Early Childhood Education (Raudhatul Athfal) throughout East Karawang District. Method. The research method used was a qualitative case study design. Data were collected through participatory observation, in-depth interviews with 47 informants, and documentation studies in 12 educational units. Data were analyzed using the thematic interactive model, including data condensation, data display, and conclusion drawing. Data trustworthiness was ensured through source and method triangulation. Results. The research results show that institutions that implement excellent service management based on Islamic values ??such as transparency (amanah), caring (ihsan), and professionalism (itqan) have proven more successful in recruiting new students. Specifically, these strategies are implemented through a real-time digital-based information system, ongoing public relations communications, and the implementation of distinctive Islamic flagship programs. The strategy, which integrates Islamic values ??into the framework of Karawang Regency, has successfully fostered a high level of public trust. Conclusion. The implications of this study confirm that service management based on Islamic ethics provides a practical contribution as a superior strategic guide for educational institution managers in increasing competitiveness and sustainably fostering community loyalty. For future development, this study implies the need to institutionalize these Islamic values into standardized operating procedures (SOPs) and integrate them with digital customer relationship management (CRM) to anticipate more complex educational market shifts.